Reusing maintenance monitoring data on preventive conservation - Diulio, María de la Paz (2022)
The indoor climate of libraries and archives is determinant for the preservation of their collections, as temperature and relative humidity can trigger other damage factors. Standards and literature recommend to perform long term monitoring to understand the climatic history where the goods were kept, instead of follow rigid and arbitrary conditions. This trend is sustainable and environmentally friendly, but adds a new duty to the overloaded staff. We present two technical advices sustained in monitoring records produced to assess the HVAC equipment and reused to preservation purposes. The first is a library collection transferred from a historic building to a new building, and the second is a deposit room supplied with de-humidificators, where the analysis evidenced a very low humidity ratio. The main conclusion is that a synergetic use of monitoring data can improve the indoor climate of the collections and reduce the energy demand for preservation.